The Influence of Work Discipline and Organizational Culture on Employee Performance with Work Motivation as an Intervening Variable in the Palembang City Public Works and Spatial Planning (PUPR) Office - Kevin, Haminsyah; Asiati, Diah Isnaini; Yamaly, Fadly (International Journal of Business, Management and Economics, 2023)
This research aims to determine the influence of work discipline and organizational culture on employee performance with work motivation as an intervening variable in the Public Works and Spatial Planning Department of Palembang City. This type of research is associative. The variables used by researchers are work discipline, organizational culture, work motivation and performance. The sample in this research was 125 employees of the Public Works and Spatial Planning Department of Palembang City who were selected using cluster sampling. The data used in this research is primary data with a questionnaire data collection method. The data analysis technique used is Structural Modeling Equation (SEM) with the Lisrel Program Application. The results of this research show that: (1) work discipline has an insignificant effect on employee performance, (2) organizational culture has a positive and significant effect on employee performance, (3) work discipline has a positive and significant effect on employee work motivation, (4) organizational culture positive and significant effect on employee work motivation, (5) work motivation has a positive and significant effect on employee performance in the Palembang City Public Works and Spatial Planning department.